PENGARUH KEPUASAN PRODUK DAN PERSEPSI HARGA TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABLE INTERVENING. ( Studi Pada Minyak Goreng Sania Di Semarang ) (Students' Journal of Economic and Management, 2013)
This Research to empirically investigate the effect of product quality and price perception on consumer loyalty with consumers kepuasn as an intervening variable in consumer cooking oil sania Semarang.berdasarkan these objectives, the researcher took the title of "THE EFFECT OF PRODUCT QUALITY AND PRICE PERCEPTION OF CONSUMER LOYALTY as an intervening variable" (Study on Edible Oil Sania In Semarang). Research on the effect of price perception of product quality and customer loyalty with customer satisfaction as an intervening variable is taking a sample of 100 respondents.This study uses primary data obtained by questionnaires. The analysis in this study using 2 pieces of regression analysis model. Regression analysis model I used to analyze the effect of product quality and price on customer satisfaction. Model II regression analysis is used to analyze the effect of product quality, price, and customer satisfaction on consumer loyalty. Research results is the quality of the product and the price has a positive effect on customer satisfaction, product quality and price has a positive effect on consumer loyalty, and customer satisfaction has a positive effect on consumer loyalty. It can be seen from the standardized beta coefficient is positive all the independent variables with a significance value <0.05. Coefficient regression models adjusted R Square I is 0.529.This means that 52.9% can be explained by the perception of product quality and price.While the remaining 47.1% is explained by other variables. Coefficient regression models adjusted R Square of 0.673 II. This means that at 67.3% can be explained by the perception of product quality and price. While the remaining 32.7% is explained by other variables such as quality of service and the number of competitors. Keywords: product quality, perceived price, customer satisfaction, customer loyalty